Beginning SQL Server 2005 Express for Developers - Dewson, Robin (Apress, 2012)
Beginning SQL Server 2005 Express for Developers is for those people who see themselves as becoming either developers, database administrators, or a mixture of both but have yet to tread that path with SQL Server 2005. This edition of my book Beginning SQL Server 2005 for Developers is for readers who wish to learn and develop on the free version of SQL Server 2005, SQL Server 2005 Express. Whether you have no knowledge of databases, or have knowledge of desktop databases such as MS Access, or even come from a server-based background such as Oracle, this book will provide you with the insight to get up and running with SQL Server 2005 Express. Right from the start, your basic knowledge will be expanded, and you will soon be moving from a perceived beginner through to a competent and professional developer. It is the aim of this book to cater to a wide range of developers, from those who prefer to use the graphical interface for as much work as possible to those who want to become more adept at using SQL Server 2005 Express’s programming language, T-SQL. Where practical, each method of using SQL Server 2005 Express is demonstrated, explained, and expanded so that you can evaluate what works best in your situation. There are plenty of examples within the book of every action along with details about the security of your data. You will also learn the best way to complete a task and even learn how to make the correct decision when there are two or more choices that could be made. Once you reach the end of this book, you will be able to design and create solid and reliable database solutions competently and proficiently.